Fixed Point, Data Dependence, and Well-Posed Problems for Multivalued Nonlinear Contractions - Iram Iqbal; Nawab Hussain; Hamed H. Al-Sulami; Shanza Hassan (Journal of Function Spaces)
The aim of the paper is to discuss data dependence, existence of fixed points, strict fixed points, and well posedness of some multivalued generalized contractions in the setting of complete metric spaces. Using auxiliary functions, we introduce Wardowski type multivalued nonlinear operators that satisfy a novel class of contractive requirements. Furthermore, the existence and data dependence findings for these multivalued operators are obtained. A nontrivial example is also provided to support the results. The results generalize, improve, and extend existing results in the literature.